The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1046/j.1420-9101.2003.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Closing of the Tethys Sea and the phylogeny of Eurasian killifishes (Cyprinodontiformes: Cyprinodontidae)

Abstract: To test vicariant speciation hypotheses derived from geological evidence of the closing of the Tethys Sea, we reconstruct phylogenetic relationships of the predominantly fresh-water killifish genus Aphanius using 3263 aligned base pairs of mitochondrial DNA from samples representing 49 populations of 13 species. We use additional 11 cyprinodontid species as outgroup taxa. Genes analysed include those encoding the partial 12S and 16S ribosomal RNAs; transfer RNAs for valine, leucine, isoleucine, glutamine, meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
165
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(178 citation statements)
references
References 62 publications
10
165
3
Order By: Relevance
“…This observation emphasizes the very interesting position of Turkey and the Middle East, as a whole, as an area of major crossroads of distinct biogeographic influences (Durand et al, 2002;Hrbek and Meyer, 2003).…”
Section: Discussionmentioning
confidence: 58%
“…This observation emphasizes the very interesting position of Turkey and the Middle East, as a whole, as an area of major crossroads of distinct biogeographic influences (Durand et al, 2002;Hrbek and Meyer, 2003).…”
Section: Discussionmentioning
confidence: 58%
“…The divergence times were estimated based on a substitution rate of 0.76% pair-wise sequence divergence per million years estimated for leuciscine fishes by Zardoya and Doadrio (1999). The estimated timing of diversification of Anatolian Pseudophoxinus corresponds closely to that of Aphanius (14.1 million years, geological calibration independent of Pseudophoxinus; Hrbek and Meyer, 2003) occupying the same geographic areas. Similarly, the pattern of low levels of intra clade III divergence in Aphanius (Hrbek et al, 2002) is also observed in Pseudophoxinus (0.6% average pair-wise sequence divergence).…”
Section: Phylogenetic Relationshipsmentioning
confidence: 99%
“…The allozymic and morphological investigations have all demonstrated a notable diVerentiation of the populations; analogously, the analysis of the highly variable D-loop tract of the mitochondrial DNA (Tigano et al 2004a, b) has indicated a strong genetic divergence between three Sicilian populations of this species. On the other hand, the molecular analysis carried out by Hrbek and Meyer (2003) showed that there is limited structuring of A. fasciatus populations; however, authors who analysed various species of the genus Aphanius, considered mitochondrial genes more useful for studies above the species level. While the allozyme studies indicate that, in some cases, there is indeed genetic divergence of the populations in relation to their geographic distribution (Maltagliati 1998a(Maltagliati , 1999, other studies both based on allozymic (Cimmaruta et al 2003) and morphological data (Tigano et al 2001;Ferrito et al 2003), suggest that this divergence does not relate to the geographic distance between the diVerent populations.…”
Section: Introductionmentioning
confidence: 99%